ANALISIS DETERMINAN KESEJAHTERAAN LANSIA DI KOTA DENPASAR - Prayoga Putra, I Putu Gede Wira; Sudibia, I Ketut (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.12.NO.12.TAHUN.2023DO - 10.24843/EEB.2023.v12.i12.p06, 2023)
The increasing problems of the elderly certainly require special attention and handling in the development process. The aim of this study; 1) analyze the simultaneous effect of education level, income, access to health, intensity of sama braya, and level of religiosity on the welfare of the elderly; 2) analyze the partial effect of education level, income, access to health, intensity of braya samam, and level of religiosity on the welfare of the elderly; 3) to analyze the role of the level of religiosity in moderating the intensity of braya meditation on the welfare of the elderly. The population in this study consisted of 66,458 people aged 60 years and over in Denpasar City so that a total sample of 155 people was obtained. Sampling was carried out by accidental sampling with structured interview methods and in-depth interviews and data analysis using moderation regression analysis. The research results show; 1) level of education, income, access to health, intensity of sama braya, and level of religiosity simultaneously have a significant effect on the welfare of the elderly; 2) level of education, income, access to health, intensity of menyama braya, and level of religiosity partially have a significant positive effect on the welfare of the elderly; 3) the level of religiosity moderates/weakens the influence of the intensity of the braya samamas on the welfare of the elderly.